2016
DOI: 10.1074/jbc.m115.700070
|View full text |Cite
|
Sign up to set email alerts
|

Chaperonin-containing T-complex Protein 1 Subunit ζ Serves as an Autoantigen Recognized by Human Vδ2 γδ T Cells in Autoimmune Diseases

Abstract: Human γδ T cells recognize conserved endogenous and stress-induced antigens typically associated with autoimmune diseases. However, the role of γδ T cells in autoimmune diseases is not clear. Few autoimmune disease-related antigens recognized by T cell receptor (TCR) γδ have been defined. In this study, we compared Vδ2 TCR complementarity-determining region 3 (CDR3) between systemic lupus erythematosus (SLE) patients and healthy donors. Results show that CDR3 length distribution differed significantly and disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Recently, it has been reported that γδT cells with NK cell–associated markers (including CD56 + T cells of the γδ type) are associated with renal fibrosis [63]. Our investigation showed that after stimulation with IL-2, IL-12, and IL-15, γδT cells, both with and without CD56 expression, exerted strong cytotoxicity against renal tubular epithelial cells, supporting a previous study [64] and further clarifying the pathogenesis of these cells.…”
Section: Cd56+ T Cells Act As Human Nkt Cells In Kidney Injurysupporting
confidence: 89%
“…Recently, it has been reported that γδT cells with NK cell–associated markers (including CD56 + T cells of the γδ type) are associated with renal fibrosis [63]. Our investigation showed that after stimulation with IL-2, IL-12, and IL-15, γδT cells, both with and without CD56 expression, exerted strong cytotoxicity against renal tubular epithelial cells, supporting a previous study [64] and further clarifying the pathogenesis of these cells.…”
Section: Cd56+ T Cells Act As Human Nkt Cells In Kidney Injurysupporting
confidence: 89%
“…Tubulin was coded by TUBA1B (tubulin alpha 1b), the principal constituent of microtubules. Furthermore, CCT6A is associated with T cell reduction in cytotoxicity, immune function loss, and reduced T cell cytotoxicity during exhaustion with prolonged exposure to tumor antigens ( 28 ). In our Reaction pathway analysis, CCT6A played a role in forming tubulin folding intermediates via CCT/TriC formation of tubulin folding intermediates by CCT/TriC.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated this hypothesis. [16][17][18][19] This study provides substantial evidence focus on TCR γδ repertoire to support this hypothesis.…”
Section: Discussionmentioning
confidence: 54%